The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/oemed-2013-101961
|View full text |Cite
|
Sign up to set email alerts
|

Green spaces and adverse pregnancy outcomes

Abstract: This study confirms the results of a few previous studies demonstrating an association between maternal proximity to green spaces and birth weight. Further investigation is needed into the associations with VLBW and VPTD, which has never been studied before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
97
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 22 publications
2
97
1
Order By: Relevance
“…Studies generally involved birth registries where the mother's address at birth was linked to a measure of greenness, most commonly NDVI, and birth outcomes were assessed from medical records that presented few opportunities for systematic bias. Positive associations between greenness and birth weight were reported consistently across the majority of studies (31, 69-72). Other studies found that higher greenness exposure was linked to lower odds of a child being small for gestational age or preterm (31), larger head circumferences (68), and lower infant mortality risk (73), although these findings were not replicated across studies.…”
Section: Introductionmentioning
confidence: 70%
“…Studies generally involved birth registries where the mother's address at birth was linked to a measure of greenness, most commonly NDVI, and birth outcomes were assessed from medical records that presented few opportunities for systematic bias. Positive associations between greenness and birth weight were reported consistently across the majority of studies (31, 69-72). Other studies found that higher greenness exposure was linked to lower odds of a child being small for gestational age or preterm (31), larger head circumferences (68), and lower infant mortality risk (73), although these findings were not replicated across studies.…”
Section: Introductionmentioning
confidence: 70%
“…For example, the distribution of urban green space is largely connected with racial and socio-economic patterns, where areas with a lower minority population and higher average incomes tend to have more recreation green space [23]. Green space is an important consideration, as it has been linked to improved pregnancy outcomes through decreasing the risk of low birth weight [24][25][26], small for gestational age [27], and preterm birth [28]. Recognizing the influence and need for such positive social environments and policies to support physical activity are further highlighted in Healthy People 2020 [29].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, that surrounding greenness was most strongly related to birth weight for women of low socioeconomic status (SES) or living in low SES areas1 4 5 has been attributed to lower SES groups spending more time in their home neighbourhood 4. Thus, the greenness measures used will represent exposure better for some women than others, and Agay-Shay and colleagues’ assertion that any exposure misclassification in their study is random is not supported.…”
mentioning
confidence: 99%
“…Agay-Shay and colleagues analyse a large Israeli birth cohort to address whether birth outcomes were related to levels of ‘surrounding greenness’ (ie, density of vegetation) around the mother's place of residence 1. Their study builds on the existing green space and health literature,2 and contributes to recent explorations of whether maternal exposure to green space might benefit the unborn child 3–7.…”
mentioning
confidence: 99%
See 1 more Smart Citation